Trust: some of its rituals - Quezada-Macchiavello, Óscar (2009)
Man must believe in order to make sense of that which he knows. We exist in believes, from which the modality of “believe” is that which maintains the silence of the other modalities making all of society, fundamentally, trust. This brief essay centers its attention on the repetition, fixation and ritual ization phenomena, which means, the stereotypes used by the subject for incising its discursive programming. These empowerment elements are in the memory; this way, the believe appears in a “tonic” and “intensive” version of that empowerment, while the “type” and “ritual” are its “atonic” and “extensive” version. It’s not strange, that, when the believe its weakened its covered by automatic rituals.